TEACHING A SECOND OR FOREIGN LANGUAGE BASED ON LITERACY NOTIONS - Dwika Herdiawan , Rama (Wiralodra English Journal, 2017)
Nowadays, litearcy has become the most prominent issue which must be paid attention in terms of second or foreign language teaching. In addition, this can be a prospective paradigm for the purpose of building the innovative teaching and learning process as well as enhancing the studetns? schemata in relation to reading and writing particularly. Therefore, this study is aimed to describe as well as prove whether the notions of literacy is appropriate or not for teaching second or foreign language, on the other hand, it also presents a number of relevant theories and also previous studies which reflect notions of literacy its self. However, there are still handicaps as well as constraints towards the implementation of literacy in terms of non native language teaching, the finding in various studies show the evidences which are related to the function of literacy as supplementary sucject or course in certain schools or colleges. Regarding the study, literacy is considered to be the affective as well as innovative strategy that can function to assist the students in acquiring the second or foreign language. Thus, notions of literacy not only conveys the traditional limits of reading and writing skills but also beyond the skills of text-centric literary interpretation.